ANALISIS BAHASA ANAK BERDASARKAN TINDAK TUTUR ASERTIF DALAM LINGKUP KELUARGA - Felisa, Nadia; Zafira, Dhiya Ulhaq; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Language plays a crucial role in developing children's social skills from an early age. The family is the first and most influential environment for language acquisition and the development of children's pragmatic abilities. This study aims to describe the forms and functions of assertive speech acts used by children in family interactions and to understand the factors influencing their use. This study employed a qualitative descriptive method with a discourse analysis approach. Data were obtained through direct observation, recordings of natural conversations between children and their families, and informal interviews with family members. The analysis was based on the assertive speech act theory proposed by Searle (1979). The results show that children use assertive speech acts in various forms, such as expressing opinions, providing information directly, and politely refusing requests. These utterances reflect children's ability to convey thoughts, feelings, and facts clearly and logically. The primary factor influencing the use of assertive speech acts is open and supportive family communication patterns. Therefore, the family environment plays a crucial role in shaping children's assertive language skills.